Molecular Imaging of Tumor-Infiltrating Macrophages in a Preclinical Mouse Model of Breast Cancer - Sun, Xianlei (Theranostics, 2015)
Significant evidence has indicated that tumor-associated macrophages (TAMs) play a critical role in the proliferation, invasion, angiogenesis, and metastasis of a variety of human carcinomas. In this study, we investigated whether near-infrared fluorescence (NIRF) imaging using a macrophage mannose receptor (MMR; CD206)-targeting agent could be used to noninvasively visualize and quantify changes in TAMs in vivo. The CD206-targeting NIRF agent, Dye-anti-CD206, was prepared and characterized in vitro and in vivo. By using NIRF imaging, we were able to noninvasively image tumor-infiltrating macrophages in the 4T1 mouse breast cancer model. Importantly, longitudinal NIRF imaging revealed the depletion of macrophages in response to zoledronic acid (ZA) treatment. However, ZA alone did not lead to the inhibition of 4T1 tumor growth. We therefore combined anti-macrophage ZA therapy and tumor cytotoxic docetaxel (DTX) therapy in the mouse model. The results demonstrated that this combination strategy could significantly inhibit tumor growth as well as tumor metastasis to the lungs. Based on these findings, we concluded that CD206-targeted molecular imaging can sensitively detect the dynamic changes in tumor-infiltrating macrophages, and that the combination of macrophage depletion and cytotoxic therapy is a promising strategy for the effective treatment of solid tumors.